Effects and Safety of Sitagliptin in Non-Alcoholic Fatty Liver Disease: A Systematic Review and Meta-Analysis - Zhang, Yuhan; Cai, Tian; Zhao, Junyu; Guo, Congcong; Yao, Jinming; Gao, Peng; Dong, Jianjun; Liao, Lin (Hormone and Metabolic Research, 2020)
Non-alcoholic fatty liver disease (NAFLD) is currently the most common cause of chronic liver disease. However, the treatment is limited. The aim of this meta-analysis was to evaluate the effects and safety of sitagliptin, a selective inhibitor of dipeptidyl peptidase-4 (DPP-4I), in treating NAFLD. Studies were sourced from electronic databases including PubMed, CENTRAL (Cochrane Controlled Trials Register), Embase, Medline, Web of Science, Clinical Trials, and CNKI to identify all randomized controlled clinical trials (RCTs) and non-RCTs in adult patients with NAFLD. Key outcomes were changes in serum levels of liver enzymes and improvement in hepatic histology and fat content measured by imaging or liver biopsy. Stata14.0 and RevMan5.3 were used for the meta-analysis. Seven studies with 269 NAFLD patients were included. Compared to the control group, sitagliptin treatment improved serum gamma-glutamyl transpeptidase (GGT) levels in the RCT subgroup (SMD = 0.79, 95% CI: 0.01–1.58). However, there was no significant improvement in serum alanine aminotransferase (ALT) or aspartate aminotransferase (AST) levels following sitagliptin treatment. Four of the included studies performed liver imaging, but sitagliptin treatment did not result in a significant reduction in liver fat content. Only five participants developed sitagliptin-related gastrointestinal discomfort. Our study suggests that sitagliptin effects individuals with NAFLD by improving serum GGT. Although sitagliptin is safe and well tolerated in NAFLD patients, it exerts no beneficial effects on liver transaminase and liver fat content in these patients.
Keywords: Sitagliptin; non-alcoholic fatty liver disease; NAFLD; DPP-4; meta-analysis